IMPLEMENTASI PERJANJIAN KERJA WAKTU TERTENTU (PKWT) DALAM HUBUNGAN KERJA DI INDONESIA - Fithriatus Shalihah (Jurnal Selat, 2016)
The law governing about employment in Indonesia is Act No. 13 of 2003. Basic of the employment relationship is working contract. Employment contract is divided into two types, namely employment contract limited time (PKWT) and the Employment contract for an unlimited time (PKWTT). Workers' rights have often been ignored. Implementation of a limited time employment contract (PKWT) in labor relations according to Law No. 13 of 2003 on Employment in Indonesia has not run in accordance with applicable regulations. For the business sector in the many city in Indonesia, relatively fewer offenses committed by employers related to the provision of workers' rights. However, the opposite occurred in the area. Employers have ignored the maximum time limit allowed by Act No. 13 of 2013 on Employment about PKWT time period. Granting rights of workers given time such as wages, hours of work and social security is still not met expectations. Constraints in the implementation of PKWT according to Law No. 13 of 2003 lies in two things, the first factor on the implementation PKWT rules that do not conform to the requirements. Employers may not recruit workers for something that is not needed in the course of the company. Most of the type and nature of the work required is the work that goes into the core work of the production process and are fixed. So in this case there has been a violation of article 59 fatal Employment Act, which is caused by the object of the work that is prohibited by the provisions of law to PKWT. Judging from the facts given time workers should have switched the status of a PKWTT, because they have been doing work that is fixed. The second factor, the omission of the deviation PKWT provisions in the employment relationship is also caused by very lax government oversight of the reality on the ground and nothing punishment on article 59. Keywords: PKWT (Employment Contract Limited Time), Work Relationship, Labour Law Penerapan perjanjian kerja waktu tertentu (PKWT) dalam hubungan kerja menurut Undang-Undang Nomor 13 tahun 2003 tentang Ketenagakerjaan belum berjalan sesuai dengan ketentuan yang berlaku. Pengusaha telah mengabaikan batas waktu maksimal yang diperkenankan oleh Undang-Undang Nomor 13 tahun 2013 tentang Ketenagakerjaan tentang masa waktu PKWT. Pemberian Hak-hak pekerja waktu tertentu seperti upah, jam kerja maupun jaminan sosial tenaga kerja juga masih belum memenuhi harapan. Hal ini merupakan pelanggaran terhadap hak asasi pekerja sebagai warga negara Indonesia yang hak-hak dasarnya telah dilindungi di dalam Undang-Undang Ketenagakerjaan RI. Kendala dalam pelaksanaan PKWT menurut Undang-Undang Nomor 13 Tahun 2003 terletak pada dua hal, pertama faktor aturan tentang pelaksanaan PKWT yang tidak sesuai dengan kebutuhan lapangan kerja. Pengusaha tidak mungkin melakukan perekrutan pekerja untuk sesuatu yang tidak dibutuhkan dalam berjalannya perusahaan. Sebagian besar jenis dan sifat pekerjaan yang dibutuhkan adalah pekerjaan yang masuk dalam pekerjaan inti dari proses produksi dan sifatnya tetap. Sehingga dalam hal ini telah terjadi penyimpangan yang cukup fatal terhadap Pasal 59 Undang-Undang Ketenagakerjaan, yang diakibatkan oleh obyek pekerjaan yang dilarang oleh ketentuan undang-undang untuk PKWT. Kata kunci: Hubungan Kerja, Hukum Ketenagakerjaan, PKWT (Perjanjian Kerja Waktu Tertentu)